Association between Treatment for Localized Prostate Cancer and Mental Health Outcomes. Issue 5 (3rd May 2022) - Luckenbaugh, Amy N.; Wallis, Christopher J. D.; Huang, Li-Ching; Wittmann, Daniela; Klaassen, Zachary; Zhao, Zighuo; Koyama, Tatsuki; Laviana, Aaron A.; Conwill, Ralph; Goodman, Michael; Hamilton, Ann S.; Wu, Xiao-Cheng; et al.
Abstract : Purpose: We aimed to compare patient-reported mental health outcomes for men undergoing treatment for localized prostate cancer longitudinally over 5 years. Materials and Methods: We conducted a prospective population-based analysis using the Comparative Effectiveness Analysis of Surgery and Radiation (CEASAR) study. Patient-reported depressive symptoms (Centers for Epidemiologic Studies Depression [CES-D]) and domains of the Medical Outcomes Study 36-item Short Form survey evaluating emotional well-being and energy/fatigue were assessed through 5 years after treatment with surgery, radiotherapy (with or without androgen deprivation therapy) and active surveillance. Regression models were adjusted for outcome-specific baseline function, demographic and clinicopathological characteristics, and treatment approach. Results: A total of 2, 742 men (median [quartiles] age 64 [59–70]) met inclusion criteria. Baseline depressive symptoms, as measured by the CES-D, were low (median 4, quartiles 1–8) without differences between groups. We found no effect of treatment modality on depressive symptoms (p=0.78), though older age, poorer health, being unmarried and baseline CES-D score were associated with declines in mental health. There was no clinically meaningful association between treatment modality and scores for either emotional well-being (p=0.81) or energy/fatigue (p=0.054). Conclusions: This prospective, population-based cohort study of men with localized prostate cancer showed no clinically important differences in mental health outcomes including depressive symptoms, emotional well-being, and energy/fatigue according to the treatment received (surgery, radiotherapy, or surveillance). However, we identified a number of characteristics associated with worse mental health outcomes including: older age, poorer health, being unmarried, and baseline CES-D score which may allow for early identification of patients most at risk of these outcomes following treatment.